The state of the art of Education for Immigrants - de Carvalho Alves Braga, Adriana (Pontifícia Universidade Católica de São Paulo, 2020)
In this article we analyze the theoretical field of Education for immigrants through academic production related to the area, with the aim of uncovering the main challenges, barriers and possibilities that the immigrant presence awakens in the educational debate. The exploratory research was carried out in repositories of theses and dissertations of a University of São Paulo, and six dissertations were selected, whose contents were analyzed. The result of this survey is capable of revealing aspects such as: the trajectory of the conquest of the right to education, xenophobic practices, relations between immigrant and national students, the perspective of teachers. These are works that include the short stays and breaks promoted by the presence of immigrant students in schools.